Rockfall hazard and risk assessment in the Yosemite Valley, California, USA - Guzzetti, F.; Reichenbach, P.; Wieczorek, G. F. (Natural hazards and earth system sciences, 2003)
Rock slides and rock falls are the most frequent types of slope movements in Yosemite National Park, California. In historical time (1857–2002) 392 rock falls and rock slides have been documented in the valley, and some of them have been mapped in detail. We present the results of an attempt to assess rock fall hazards in the Yosemite Valley. Spatial and temporal aspects of rock falls hazard are considered. A detailed inventory of slope movements covering the 145-year period from 1857 to 2002 is used to determine the frequency-volume statistics of rock falls and to estimate the annual frequency of rock falls, providing the temporal component of rock fall hazard. The extent of the areas potentially subject to rock fall hazards in the Yosemite Valley were obtained using STONE, a physically-based rock fall simulation computer program. The software computes 3-dimensional rock fall trajectories starting from a digital elevation model (DEM), the location of rock fall release points, and maps of the dynamic rolling friction coefficient and of the coefficients of normal and tangential energy restitution. For each DEM cell the software calculates the number of rock falls passing through the cell, the maximum rock fall velocity and the maximum flying height. For the Yosemite Valley, a DEM with a ground resolution of 10 × 10 m was prepared using topographic contour lines from the U.S. Geological Survey 1:24 000-scale maps. Rock fall release points were identified as DEM cells having a slope steeper than 60°, an assumption based on the location of historical rock falls. Maps of the normal and tangential energy restitution coefficients and of the rolling friction coefficient were produced from a surficial geologic map. The availability of historical rock falls mapped in detail allowed us to check the computer program performance and to calibrate the model parameters. Visual and statistical comparison of the model results with the mapped rock falls confirmed the accuracy of the model. The model results are compared with a previous map of rockfall talus and with a geomorphic assessment of rock fall hazard based on potential energy referred to as a shadow angle approach, recently completed for the Yosemite Valley. The model results are then used to identify the roads and trails more subject to rock fall hazard. Of the 166.5 km of roads and trails in the Yosemite Valley 31.2% were found to be potentially subject to rock fall hazard, of which 14% are subject to very high hazard.